IBM KELOMPOK TANI LIDAH BUAYA - Sri Rahayu Prastyaningsih; Ambar Tri Ratnaningsih; Dedi Zargustin (Universitas Lancang Kuning, 2017)
The cultivation of aloe vera plants began since residents in Pekanbaru know of the benefits of aloe vera plant. The group of Lidah Buaya Kita was formed in January 2014 in the District Rumbai, Pekanbaru City, Riau Province. The first time, farmers only sell seedling and leaves of aloe vera, then they make crackers and tea from leaves its own garden, where product of crackers and tea can add value to the business as one of product processed of the aloe vera plant. Partners also requested training for make drinks aloe vera. The aims of this IBM (1) make drinks aloe vera (2) techniques of processing crackers use machine flour mixer (3) Products get permits from the Dinas Kesehatan (4) analyze the nutrients and chemical of crackers and tea product (5) Make packaging of drinks, crackers and tea aloe vera (6) the promotion and marketing of aloe vera products (7) business analysis of product.IbM was implemented in 2016. Our Patners was aloe vera farmers in (1) RW 02 kelurahan Lembah Damai (2) RW 04 kelurahan Lembah Sari. The result of our IbM was (1) the partner be able to make a drink aloe vera. (2) partners have cup sealer and flour mixer machine to support their production. (3) partner has the brand, license P-IRT and test nutrient/chemical content (4) the partner is able to package the aoe vera product and ready for market (5) partners can promote aloe vera product.The cultivation of aloe vera plants began since residents in Pekanbaru know of the benefits of aloe vera plant. The group of Lidah Buaya Kita was formed in January 2014 in the District Rumbai, Pekanbaru City, Riau Province. The first time, farmers only sell seedling and leaves of aloe vera, then they make crackers and tea from leaves its own garden, where product of crackers and tea can add value to the business as one of product processed of the aloe vera plant. Partners also requested training for make drinks aloe vera. The aims of this IBM (1) make drinks aloe vera (2) techniques of processing crackers use machine flour mixer (3) Products get permits from the Dinas Kesehatan (4) analyze the nutrients and chemical of crackers and tea product (5) Make packaging of drinks, crackers and tea aloe vera (6) the promotion and marketing of aloe vera products (7) business analysis of product.IbM was implemented in 2016. Our Patners was aloe vera farmers in (1) RW 02 kelurahan Lembah Damai (2) RW 04 kelurahan Lembah Sari. The result of our IbM was (1) the partner be able to make a drink aloe vera. (2) partners have cup sealer and flour mixer machine to support their production. (3) partner has the brand, license P-IRT and test nutrient/chemical content (4) the partner is able to package the aoe vera product and ready for market (5) partners can promote aloe vera product